Evolution of transformation characteristics with heating/cooling rate in NiTi shape memory alloys - Nurveren, K.; Akdogan, A.; Huang, W. M. (ELSEVIER SCIENCE SA, 2008)
The martensitic transformation behavior, morphology and transition temperatures in NiTi-based shape memory alloys (SMAs) are strongly influenced by thermo-mechanical treatments. The present work aims to study the influence of heating/cooling rate on the transformation characteristics of a near-equiatomic NiTi SMA. There is a critical annealing temperature range where the transformation characteristics measured in the NiTi SMA are remarkably different. The changes in the transformation characteristics at different heating/cooling rates were studied by means of differential scanning calorimeter (DSC) measurements for four NiTi SMAs, which were made of the same raw material but heat-treated below and above the critical temperature. The results showed that the heating/cooling rate has strong influence on the transformation temperatures, the absorbed/released heat, and the elastic and irreversible energies during transformation. (c) 2007 Elsevier B.V All rights reserved.
Keywords: NiTi shape memory alloy; differential scanning calorimetry (DSC); heating and cooling rate; phase transformation; transformation characteristic; BEHAVIOR; TEMPERATURE; DEPENDENCE; Engineering; Materials Science